Pemanfataan EM4 Pada Kompos dan FMA Terhadap Pertumbuhan Rumput Kumpai (Hymenachne amplexicaulis (Rudge) Ness.) - Hidayat, R; Syafria, H; Adriani, A; Lestari, W M (Politeknik Negeri Lampung, 2024)
The aim of this research is to determine the use of EM4 in compost and AMF (Fungi, Mycorrhiza, Arbuscula) on the growth of kumpai grass on ex-coal mining land. The research phase used CRD which consisted of 4 treatments and 4 replications, where P0 = 40% feces + 35% empty fruit bunches + 20% palm fronds + 4% bran + 1% urea, P1 = P0 + 2% EM4, P2 = P0 + 4% EM4, P3= P0 + 6% EM4. pH parameters, and (C, N, P, K and C/N ratio) of compost. The best of one step is used on two steps. This research was carried out in two stages using CRD with a 3x2x3 factorial pattern, with 2 factors as treatment, namely factor A was A0= 0 compost, A1= 12 g compost, and A2= 24 g compost and factor B was AMF with a dose of B0= 0 g and B1= 20 grams. The treatments analyzed included plant height, number of tillers, root dry weight and forage dry matter yield. The results showed that EM4 treatment had no effect on shrinkage components, pH, P and K (P<0.05). Compost average shrinkage= 21.37%, pH= 7, N= 3.66%, P= 0.48%, C= 29.94%, K= 1.14% and C/N= 12.03 . EM4 treatment had a significant effect on the composition of C, N and C/N. In stage 2 the research results showed that the treatment given AMF 20 g had a significant effect on plant height, number of tillers, and forage dry matter yield. Meanwhile, the interaction between composition and FMA has no significant effect on all variables. The conclusions of this research are (1) the addition of EM4 starter at a level of 6% shows the best value for compost shrinkage, pH and compost nutrient content. (2) Giving 20 g AMF increases forage growth.